Determinación de capacidad antioxidante del néctar funcional a partir de papaya (Carica papaya), Carambola (Averrhoa carambola) y Camu Camu (Myrciaria dubia) - Saurin del Aguila, Zadith (2025)
Fruits such as papaya (Carica papaya), star fruit (Averrhoa carambola) and camu camu (Myrciaria dubia) are seasonal fruits from the Amazon region of Peru, characterized by their high content of bioactive compounds such as vitamin C, vitamin A, antioxidants and tocopherols. This study was carried out entirely in the laboratories of the Amazonian Natural Resources Research Center of the UNAP. using the Peruvian Food Composition Tables (2025) for the nutritional characterization of raw materials, the antioxidant capacity was evaluated using the -2-2-diphenyl-1-picrylhydracil methodology, using 517 nanometers, the gallic acid content was determined following the method described by Folin - Ciocalteu, Graphs of percentage of antioxidant (PA%) versus concentration of -2-2 diphenyl-1-picrylhydracil were also elaborated, and % activation vs total phenol content for each fruit, subsequently, a functional nectar was developed by combining the three fruits, using three different formulations (1:1:7, 1:1:6, 1:1:5), in accordance with the guidelines of NTP 203.110:2002, The physicochemical analyses of the best treatment reported: 7.00 degrees brix, total heartburn (C6H8O7): 0.21 %, pH (25oC): 4.49 and vitamin C content of 110.00 mg/100 Ml, the microbiological analysis showed counts 0.05).